The etiology and incidence of hypokalemia in intensive care unit - (:unkn) unknown (My University, 2003)
Objective: Hypokalemia, a frequent electrolyte imbalance encountered in the Intensive Care Unit (ICU), is an important cause of morbidity and mortality in critically ill patients. In this study the etiology and incidence of hypokalemia in critically ill patients was investigated retrospectively. Methods: The ICU records of 440 patients, followed up more than 2 days in surgical intensive care and reanimation unit between 01.01.1999 and 31.12.2000 were analysed retrospectively. When hypokalemia was first observed (K<3.5 meq/L) in patients, the coexisting pathologies such as hypothermia (axillary body temperature <36°0), dialysis, presence of diarrhea, vomiting and ketoacidosis, arterial pH values, type of nutrition, use of insulin, diuretics and beta adrenergic agents, presence of blood transfusions were recorded. The relationship between these data, age, type of surgery and hypokalemia was recorded. The data obtained were compared statistically with ANOVA, Fisher's exact and Chi-square tests (p<0.05). Results: In 192 of 440 patients (40%) hypokalemia was found for the first time on 2.3±1.3th day of their ICU stay. The incidence of hypokalemia concerning the type of surgery was found as 59% in radical cystectomies, 51% in vascular craniotomies, 50% in radical prostatectomies and 47% in tumoral craniotomies. The relationship between hypokalemia and clinical findings, and the medications used are found significant (p<0.05). In the presence of metabolic alkalosis, the incidence of hypokalemia was 76%. Hypokalemia incidence in patients receiving enteral or parenteral nutrition was twice that of patients receiving oral nutrition. Conclusion: Causes and incidence of hypokalemia must be established and follow up of plasma potassium levels should be done frequently in critically ill patients in the high risk group. This will decrease the mortality and morbidity with early replacement therapy.
Keywords: Electrolyte imbalance; Hypokalemia; Intensive Care Unit